SPORT PSYCHOMETRY, PARTICIPANTS AND INVARIANCE: A CRITICAL REVIEW - Rebustini, Flávio; Balbinotti, Marcos Alencar Abaide; Ferretti-rebustini, Renata Eloah De Lucena; Machado, Afonso Antonio (Universidade Estadual de Maringá, 2016)
ABSTRACT This article presents a critical review of how sporting context variables and participants may affect the validity evidence of measurement instruments. Despite the literature presenting, there is significant effect of gender, age, practice time, length of experience, sporting experience, stages, training loads, competition, as well as socioeconomic and educational level, among other psychological variables, little has been explored about such effects. Recurrent studies have basically reported age, gender and sport. The absence of control of this information in the sporting context and the participant can cause measurement inaccuracy, limitation in application, errors in interpretations and inappropriate interventions, loss of reproducibility and limitations in comparative studies. Furthermore, it prevents analysis of invariance, compromising their stability. Thus, it is urgent and mandatory to tighten the range of indicators that characterize the participants and the context of studies in sports.

RESUMO Este artigo apresenta uma revisão crítica de como as variáveis do contexto esportivo e dos participantes podem afetar a busca por evidências de validade dos instrumentos de medida. Apesar da literatura apontar que fatores como sexo, idade, tempo de prática, tempo de experiência, experiências esportivas, fases e regimes de treinamento e competição, nível socioeconômico e educacional, dentre outros têm um efeito importante nas variáveis psicológicas, pouco tem se explorado sobre tal efeito. Recorrentemente, os estudos têm reportado basicamente a idade, sexo e modalidade esportiva. A ausência do controle dessas informações sobre o contexto e o participante pode provocar imprecisão das medidas, limitação da aplicação, erros de interpretação e intervenções inadequadas, perda da reprodutibilidade e limitação de estudos comparativos. Além disso, impossibilita a testagem da invariância. Desta forma, torna-se premente e mandatório um rigor maior sobre a gama de indicadores que caracterizam os participantes e o contexto dos estudos no esporte
PSICOMETRIA ESPORTIVA, CARACTERIZAÇÃO DOS PARTICIPANTES E INVARIÂNCIA: UMA REVISÃO CRÍTICA
Keywords: Psychometry; Sport; Method.; Psicometria; Esporte; Método.